HOW TO TEACH EFFECTIVE WRITING FOR NON-NATIVE ENGLISH SPEAKERS - Turgunova Shakhnoza Tursunbayevna (Western European Studies, 2025)
This aricle explores teaching effective writing to non-native English speakers presents unique challenges, but it also offers opportunities to enhance their language proficiency and academic success. This paper explores practical strategies and methods for helping non-native speakers improve their writing skills in English. Key areas of focus include building a strong foundation in grammar, sentence structure, and vocabulary, as well as fostering an understanding of coherence, cohesion, and logical flow in written work
Keywords: non-native English speakers; writing instruction